The Effect of Meta-Cognitive Strategy in Improving the Reading Comprehension of the Ninth Grade Students in North-East Badia in Jordan - Alqadi, Haitham (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aimed at identifying the impact of meta- cognitive strategy in improving the reading comprehension of the basic ninth grade in the northeastern Badia students. The questions of the study are: 1.What is the effect of the meta-cognitive strategy in improving the reading comprehension of the ninth grade students in the Northern East Badia in Jordan. 2. Does the effect of the meta-cognitive strategy in improving the reading comprehension differ according to the sex and group? The study population consisted of all students in the basic ninth grade for the academic year 2015/2016 , totaling (2316) students (1163 males and 1153 females). The study sample consisted of 80 students representing (3.45%) of the study population . Schools were selected by the stratified random simple sample, and distributed to the six study schools. For the purposes of the study, the researcher prepared a teaching model as meta-cognitive strategy to improve reading comprehension, and a test was prepared for this purpose to measure the students’ ability to improve reading comprehension , and the test consisted of 10 open-ended questions . After being collected, data have been processed using statistical and descriptive methods. Means, and standard deviations were estimated ; the researcher also used statistical and analytical methods including (ANCOVA). The study revealed the following results: The lack of significant differences between school groups attributed to the gender of the students variable differences, and the presence of statistically significant differences between the experimental school groups and control group in favor of the experimental group that studied the meta-cognitive strategy to improve reading comprehension among basic ninth grade in the North East Badia. In light of the results of this study, the researcher recommended a number of scientific and practical recommendations.